Productivity and Sustainable Consumption in OECD Countries: 1980-2005 - Dean Baker; David Rosnick (International Productivity Monitor, 2007)
Productivity growth is the main long-run determinant of living standards. However, there are some distinctions between productivity growth as conventionally measured and the potential of the economy to raise living standards. Specifically, insofar as the share of depreciation in output increases, the rate of productivity growth will exceed the potential growth rate of living standards. The same will be the case if prices for investment goods decline relative to prices for consumption goods. This article adjusts for these factors to develop the concept of “sustainable consumption,” and compares trends in this variable with productivity growth in OECD countries for the 1980-2005 period.